Isolation, identification, and characterization of corn-derived antioxidant peptides from corn fermented milk by Limosilactobacillus fermentum - Xu, Jue; Chen, Yingyan; Fan, Xiankang; Shi, Zihang; Liu, Mingzhen; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong (Frontiers in Nutrition, 2022)
Dairy-derived peptides and corn-derived peptides have been identified as essential ingredients for health promotion in the food industry. The hydrolysis based on lactic acid bacteria (LAB) protease system is one of the most popular methods to prepare bioactive peptides. The objectives of this paper are to develop antioxidant fermented milk and to obtain natural antioxidant peptides. In our study, LAB with antioxidant capacity were screened in vitro, and the corn fermented milk with antioxidant capacity was achieved by the traditional fermentation method. Fermented milk was purified by ultrafiltration and molecular sieve, and identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Our findings demonstrate that Limosilactobacillus fermentum L15 had a scavenging capacity of more than 80% of DPPH radicals, Trolox equivalent antioxidant capacity (TEAC) of 0.348 ± 0.005 mmol/L. Meanwhile, the peptide content of corn fermented milk prepared with L. fermentum L15 was 0.914 ± 0.009 mg/mL and TAEC of 0.781 ± 0.020 mmol/L. Particularly important, IGGIGTVPVGR and LTTVTPGSR isolated and extracted from fermented milk were found to have antioxidant capacity for the first time. The synthetic peptides IGGIGTVPVGR and LTTVTPGSR demonstrated a scavenging capacity of 70.07 ± 2.71% and 70.07 ± 2.77% for DPPH radicals and an antioxidant capacity of 0.62 ± 0.01 mmol/L and 0.64 ± 0.02 mmol/L Trolox equivalent, respectively. This research provides ideas and basis for the development and utilization of functional dairy products.